Influence of Grit Size and Wood Species on the Granularity of Dust Particles during Sanding - Marta Pędzik; Kinga Stuper-Szablewska; Maciej Sydor; Tomasz Rogoziński (Applied Sciences, 2020)
Wood dust poses a threat to the health of employees and the risk of explosion and fire, accelerates the wear of machines, worsens the quality of processing, and requires large financial outlays for its removal. The aim of this study was to investigate the extent to which the grit size of sandpaper influences the size of the wood dust particles and the proportion of the finest particles which, when dispersed in the air, may constitute the respirable fraction. Six species of hardwood (beech, oak, ash, hornbeam, alder, and walnut), and three species of softwood (larch, pine, and spruce) were used in the research. While sanding the samples under the established laboratory conditions, the following were measured for two types of sandpapers (grit sizes P60 and P180): mean arithmetic particle size of dust and finest dust particles content (<10 µm). Based on the obtained results, we found that the largest dust particle sizes were obtained for alder, pine, and spruce; the smallest size of dust particles during sanding with both sandpapers was obtained for beech, hornbeam, oak, ash, larch, and walnut. The mean arithmetic particle sizes ranged from 327.98 µm for pine to 104.23 µm for hornbeam. The mean particle size of the dust obtained with P60 granulation paper was 1.4 times larger than that of the dust obtained with P180 granulation sandpaper. The content of the finest dust particles ranged from 0.21% for pine (P60 sandpaper) to 12.58% for beech (P180 sandpaper).The type of wood (hardwood or softwood) has a significant influence on the particle size and the content of the finest dust fraction.